Potentiation by endogenously released ATP of spontaneous transmitter secretion at developing neuromuscular synapses in Xenopus cell cultures. - Fu, W. M. (1994)
1. Previously we have shown that extracellular application of ATP, a substance co-stored and co-released with acetylcholine (ACh) in the peripheral nervous system, markedly potentiated the frequency of spontaneous synaptic currents (SSCs) produced by ACh. In the present study, we have further characterized the purinoceptor which mediates the potentiation effect of ATP and the role of endogenously released ATP. 2. Pretreatment with a P2-purinoceptor antagonist, suramin (0.3 mM), but not a P1-purinoceptor antagonist, 8-phenyltheophylline (0.1 mM), prevented the potentiating effect of ATP. 3. We studied the role of endogenously released ATP by examining the effect of a specific P2-purinoceptor antagonist on the frequency of spontaneous synaptic events at high-activity synapses (> or = 3 Hz) and found that suramin, but not 8-phenyltheophylline markedly reduced the frequency of SSCs at these high-activity synapses. In addition, desensitizing the P2-purinoceptor with alpha,beta-methylene ATP also produced similar effects to suramin. 4. Extracellular application of the L-type Ca2+ channel blockers, verapamil, nifedipine or diltiazem (10 microM each) reduced SSC frequency of high-activity synapses, while the N-type Ca2+ channel blocker, omega-conotoxin had no appreciable effect. The potentiating effect of ATP was further prevented by pretreatment with the L-type Ca2+ channel blockers. On the other hand, Bay K 8644, which is a depolarization-dependent L-type Ca2+ channel agonist, potentiated SSC frequency at these high-activity synapses.(ABSTRACT TRUNCATED AT 250 WORDS)